Causal Factors of Flight Delay in Nigerian Airport: A Case Study of Murtala Muhammed International Airport - Oluwafisayo T., Ayo-Agunbiade; Mobolaji S., Stephens (Bangladesh Journal of Multidisciplinary Scientific Research, 2019)
Delay is a prominent event mostly experienced at the airport by both airline and passengers. Globally delay is permitted at 15mins later than the scheduled time. Assessing the level of delay in the airport is a major criterion for measuring airport performance. Aircraft not adhering to schedule flight results in increased airport congestion, cancellation flight and flight delay. This study made use of primary data through well-structured questionnaires to obtain information from selected NAMA Staff at the Murtala Muhammed International Airport (MMIA). Operational delay report for a month and Airlines flight were examined for two months under the MMA2 to know the deviation of scheduled flight time from actual flight time. Descriptive Analysis, Wilcoxon Rank test, Factor Analysis and Step Wise Regression were the statistical tools deployed for this research. Findings showed that on a monthly base, 63% of the domestic traffic flows are delayed. Some factors responsible for delay were considered: aircraft damage, bad weather, aircraft maintenance, VIP movement and fueling are the major factor responsible for delay of aircraft Movement.